Upstream Elementary A2: Student's Book - Evans V. Virginia (Newbury, Express Publishing, 2011)
Upstream Elementary A2 is a modular secondary-level course for learners of the English language at CEF A2 level. The series combines active English learning with a variety of lively topics presented in themed units.